2008
DOI: 10.1111/j.1365-2982.2008.01132.x
|View full text |Cite
|
Sign up to set email alerts
|

Indomethacin improves locomotor deficit and reduces brain concentrations of neuroinhibitory steroids in rats following portacaval anastomosis

Abstract: Hepatic encephalopathy (HE) is a neuropsychiatric complication of both acute and chronic liver failure characterized by progressive neuronal inhibition. Some neurosteroids are potent positive allosteric modulators of the gamma-aminobutyric acid (GABA)-A receptor complex, and 'increased GABAergic tone' has been proposed to explain the neuroinhibition characteristics of HE. Brain levels of the neurosteroids pregnenolone, allopregnanolone and tetrahydrodesoxycorticosterone (THDOC) and the functional status of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
22
0
1

Year Published

2008
2008
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(25 citation statements)
references
References 58 publications
(131 reference statements)
2
22
0
1
Order By: Relevance
“…Thus, the results of this particular study do not allow the conclusion that no anxiety-related effects were found in BDL animals. Furthermore, in another study (Ahboucha et al 2008) performed with rats with portacaval anastomosis tested in the EPM, no anxiety-related effects were found, but deficits in the animals' motor behavior were observed, thus compromising any conclusion regarding anxiety parameters. On the other hand, the anxiogenic effects observed were consistent with clinical descriptions of HE patients (Butterworth 2003, Sakamoto et al 2012.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…Thus, the results of this particular study do not allow the conclusion that no anxiety-related effects were found in BDL animals. Furthermore, in another study (Ahboucha et al 2008) performed with rats with portacaval anastomosis tested in the EPM, no anxiety-related effects were found, but deficits in the animals' motor behavior were observed, thus compromising any conclusion regarding anxiety parameters. On the other hand, the anxiogenic effects observed were consistent with clinical descriptions of HE patients (Butterworth 2003, Sakamoto et al 2012.…”
Section: Discussionmentioning
confidence: 93%
“…According to the HESA, psychomotor impairment would describe a more severe grade of encephalopathy (stage 2 HE). Although in some of the studies conducted with different animal models of HE, decreases in locomotor activity were observed (Ahboucha et al 2008, Leke et al 2012, in others, no motor alterations were found (Sergeeva et al 2005). In fact, some studies have suggested that depending on the test used to measure motor activity, deficits may or may not be obtained.…”
Section: Discussionmentioning
confidence: 98%
“…The spherical adsorptive carbon AST-120, was able to reduce ammonia levels in experimental animal models [28]. HPN-100 is a pro-drug which, although not yet tested on patients with liver disease, is thought to ameliorate the clinical condition of HE.…”
Section: Biochemistry Alterations In Hementioning
confidence: 99%
“…According to current evidence, inflammatory mediators play an important role in inducing the neurophysiological brain alterations observed in patients with HE [103]. Based on this observation, experimental studies have been conducted on animal models, proving the ability of indomethacin [104] and ibuprofen [105] to ameliorate the cerebral symptoms observed in HE patients. L-methinine S-sulfoximine (MSO), an irreversible inhibitor of GS, can prove of therapeutic value for patients with HE, given the fact that it can lower brain glutamine levels and therefore prevent astrocyte swelling and cerebral edema [106].…”
Section: Treatment Of Hepatic Encephalopathymentioning
confidence: 99%